Total Reflection and Cloaking by Triangular Defects Embedded in Zero Index Metamaterials (Advances in Applied Mathematics and Mechanics, 2018)
In this work, we investigate wave propagation through a zero index metamaterial(ZIM) waveguide embedded with triangular dielectric defects. We providea theoretical guidance on how to achieve total reflection and total transmission (i.e.,cloaking) by adjusting the defect sizes and/or permittivities of the defects. Our workprovides a systematical way in manipulating wave propagation through ZIM in additionto the widely studied dielectric defects with cylindrical and rectangular geometries.